Hermes — a robust, low latency, optical link protocol for synchronous data transfer at commercial asynchronous line rates. (1st June 2022) - Adamidis, K.; Bestintzanos, I.; Foudas, C.; Howard, A.; Iles, G.M.; Mallios, S.; Williams, T.
Abstract: The CMS Level-1 Trigger at HL-LHC and associated upstream systems employ more than 10000 25 Gb/s optical links, transferring almost a Pb/s of data synchronously between the different back-end processing nodes. Stable operation of these links is essential to avoid the injection of erroneous signals into the trigger path, potentially leading to a flood of false triggers or data loss. The Hermes protocol, implemented on Xilinx UltraScale+ FPGAs, provides this stability while operating at asynchronous, industry standard line rates. The protocol design as well as results on the performance from extensive testing are presented here.